Reducing Disease Risk in Aquaculture - World Bank Group (Washington, DC, 2014)
There are thousands of rickettsial, viral, bacterial, protozoan, and metazoan parasites that cause disease in farmed aquatic animals. While the basics of farm-level disease management are known, the interconnectedness among aquaculture installations and between aquaculture and the external environment means that only a few careless farms can ruin an industry. Considering the gravity and frequency of fish disease outbreaks, guidelines on the development and implementation of national policies for their prevention, detection, and management are urgently needed. Hampering this is the lack of a comprehensive overview of the practical ways and means of regulating aquaculture that will permit both governments and aqua culturists to: (1) calculate the cost-benefit ratio of investments in disease control, and (2) find a cost-effective strategy for the implementation of best practices. The study is based on review of published and unpublished data supplied by the Chilean, Vietnamese, Malagasy, and Mozambican authorities, researchers, and local aquaculture investors and other stakeholders. The selection of case studies was guided by the need to explore disease outbreaks in a range of geographical and industrial development scenarios. The three case studies capture the breadth and depth of experience among farmers and governments confronted with catastrophic disease outbreaks in aquaculture. The overarching lesson is that successful aquaculture depends on the capacity of biological systems to support it. Defining the capacities of bodies of water is essential in order to regulate the number of farms and to set limits on the maximum production in farming areas.